Dual control of midgut trehalase activity by 20-hydroxyecdysone and an inhibitory factor in the bamboo borer Omphisa fuscidentalis Hampson - Nujira Tatun (2018)
During larval diapause lasting 9 months from September to May, trehalase activity in the midgut of the bamboo borer Omphisa fuscidentalis Hampson (Lepidoptera: Crambidae) was low from December to April, followed by a fourfold increase in May that remained high during the pupal stage in July. An application of juvenile hormone analog (JHA) produced increases in the ecdysteroid titer, while trehalase activity was increased by both JHA and 20-hydroxyecdysone (20E) injection. The trehalase activity in the midgut of diapausing larvae was doubled by incubating the midgut with 20E for 48 h. During diapause as well as after JHA application, expression of two ecdysone receptor isoform genes (EcR-A and EcR-B1) in the midgut increased simultaneously with the increase in hemolymph ecdysteroid titer, followed by an increase in trehalase activity. The hemolymph of diapausing larvae contained a trehalase inhibitor and inhibitory activity was high during diapause. After 20E injection, trehalase inhibition decreased as midgut trehalase activity increased. Taken together, at least two factors may participate in the change in midgut trehalase activity: increase in trehalase activity and decrease in trehalase inhibitor activity, both of which may be induced by 20E. © 2007 Elsevier Ltd. All rights reserved.